Navigating coexistence: perspectives of host community and Syrian refugees in Al-Mafraq, Jordan - Palash Kamruzzaman; Najah Al-shanableh; Hanaa Albanna (Cogent Social Sciences)
The influx of Syrian refugees into Al Mafraq, Jordan poses complex challenges for the host community. This study, supported by the Faculty of Business and Creative Industries (FBCI) at the University of South Wales, explores how perspectives and experiences of the host community and refugees can help to understand the enablers and challenges of their coexistence. Using a mixed-method approach, it combined qualitative focus group discussions with a quantitative online survey to assess the perspectives and experiences of these groups. The findings are presented around five key issues perceived by the host community and refugees. These include safety, security, community relations, economic conditions, and the role of international organizations. It is argued that the evidence and analysis presented in this paper can help inform policy and practice by emphasizing the importance of understanding both the host and refugee experiences. This underscores the need for inclusive national planning to promote integration, social security, and protection of all individuals in Jordan. This research highlights how recognizing and addressing host community perspectives can enhance refugee integration and foster sustainable development amidst growing tension. By challenging misconceptions and valuing the needs of both Jordanians and refugees, this study advocates a cohesive and resilient society.